(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Proposed study is to determine the suitability of Moringaoliefera as an alternative and cheap local coagulating material in the improvement of water quality in terms of turbidity, pH, and color and microorganism removal for Bhopal. This study completed in four phase and their results observed. From the phase one the results of this work indicate that bacterial deactivation can be achieved using sunlight alone and the disinfection rate was enhanced by 83 using batch reactor. The phase two results concluded that 0.5gl moringaoleifera seed powder could be used as biocoagulant to get upto 88.7 turbidity removal and 32.5 TDS reduction .pH also got reduced and came under range 6.5-8.5 as according to WHO guidelines. So, plant biocoagulant could be a better option for rural areas as this seed is easily available in villages and it is already been consumed in various food items. It could be a better replacement for harmful chemicals in treatment of water. Phase three result The Photo catalysts are showing around difference of 4 degree which is around 10 increment in the temperature which is good sign so in initial experiment we did with TiO2 and AC on which AC is showing around difference of 1 degree so it is clear that we have to use the AC and next experiment was with AC‟s amount variation and on that we got that on 27mgl is showing best result in temperature. Last phase four result Design is at its theoretical mode and design can vary according to demand and supply. A simple model of 2 L is portable and workable for one person which is that best part of this project.